2019
DOI: 10.1111/1747-0080.12563
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutrition and dietetic research: A content analysis of the past decade of Dietitians Association of Australia conference abstracts

Abstract: Aim As a sample of research outputs supported by the nutrition and dietetics profession in Australia, the present study aimed to conduct a content analysis of Dietitians Association of Australia (DAA) conference abstracts to identify themes, methods and contribution by geographical location over time. Methods Conference abstracts published during the period 2008‐2018 (excluding those from the International Congress of Dietetics in 2012) were obtained. Key outcome data including topics of research and methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This finding is consistent with a previous study in nursing where scientific activities such as research were absent in stock images (11) . Recent research has shown an increasing academic output from dietitians (17)(18)(19) , and this should be represented through authentic images of research across settings. Additionally, the majority of images were staged photographs of an individual posing with fresh fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previous study in nursing where scientific activities such as research were absent in stock images (11) . Recent research has shown an increasing academic output from dietitians (17)(18)(19) , and this should be represented through authentic images of research across settings. Additionally, the majority of images were staged photographs of an individual posing with fresh fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…ACA was applied to implement Leximancer 4.5 software [47], whereby concepts were automatically extracted from the abstracts using unsupervised seeding where the starting point of each concept (a word or concept seed) was identified based on the frequency of its occurrences in each text. Then visual concepts would be created by Leximancer after identifying meanings of text by running its own algorithms, and Leximancer takes text segment as the basic identification unit [48]. Each concept will form a thesaurus of terms by adding terms to each concept seed.…”
Section: Topic Modellingmentioning
confidence: 99%
“…In doing so, hospital foodservice can contribute to achieving the United Nations Sustainable Development Goals of "responsible consumption and production" (7). However, foodservice is often an overlooked aspect of healthcare delivery, food system, and dietetic research (8). To date, foodservice in hospitals has focused on delivering food to patients that meet their nutritional needs.…”
Section: Introductionmentioning
confidence: 99%